The Effect of the Role Playing Learning Model on the Nationalist Character of Grade XI Students of Muhammadiyah 1 Private High School Medan - Afifah Maulidia (Journal of Elementary School Education, 2026)
This study aims to determine the application of the Role Playing learning model in learning, the level of nationalism character of class XI students of Muhammadiyah 1 Medan Private Islamic Senior High School, and the influence of the Role Playing learning model on students' nationalism character. This study uses a quantitative approach with a simple linear regression method. The research sample consisted of 20 class XI students of Muhammadiyah 1 Medan Private Islamic Senior High School in the 2025/2026 Academic Year. The data collection technique used a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was carried out using IBM SPSS Statistics 22 through descriptive statistical tests, normality tests, and simple linear regression hypothesis tests. The results showed that the Role Playing learning model had a significant effect on students' nationalism character with a significance value of 0.001 (<0.05) and a calculated t value of 4.087 greater than the t table of 2.101, so that H₀ was rejected and Hₐ was accepted. Thus, the Role Playing learning model has a significant influence on the nationalism character of class XI students at Muhammadiyah 1 Medan Private Madrasah Aliyah in the 2025/2026 Academic Year.